2006
DOI: 10.1088/0029-5515/46/6/s03
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the RF source development programme at IPP Garching

Abstract: The development of a large-area RF source for negative hydrogen ions, an official EFDA task agreement, is aiming at demonstrating ITER-relevant ion source parameters. This implies a current density of 20 mA/cm 2 accelerated Dions at a source filling pressure of ≤ 0.3 Pa and an electron to ion ratio of ≤ 1 from a PINI-size extraction area for pulse lengths of up to 1 hour. The work is progressing along three lines in parallel: (i) optimisation of current densities at low pressure and electron/ion ratio, utilisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
492
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 375 publications
(526 citation statements)
references
References 29 publications
29
492
1
4
Order By: Relevance
“…In addition the original 6 mm thickness in the ITER reference design for the PG has been increased to 9 mm. These two modifications increase the area for the conversion of neutrals and positive ions to negative in the region close to the apertures and allow a more suitable starting angle of the negative ions [2].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In addition the original 6 mm thickness in the ITER reference design for the PG has been increased to 9 mm. These two modifications increase the area for the conversion of neutrals and positive ions to negative in the region close to the apertures and allow a more suitable starting angle of the negative ions [2].…”
Section: Figurementioning
confidence: 99%
“…The ESM are required to deflect the co-extracted electrons. Although these magnets are not inside the source, the experience acquired at IPP suggests that these magnets influence drastically the plasma source performance [2]. In ELISE it will be possible to align the ESM both in horizontal and vertical direction, enabling investigations of the source performance with the ESM field parallel or orthogonal to the FF.…”
Section: Electron Suppression Magnets (Esm) Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RF ion source for the ITER NBI has been designed on the basis of the existing smaller size sources being operated by the Max-Planck-Institut für Plasmaphysik in Garching [4].…”
Section: General Descriptionmentioning
confidence: 99%
“…All of these requirements have been fulfilled by the IPP prototype sources but not simultaneously: at the short pulse test facility BATMAN [4] (t beam ≤ 4 s, one pulse each 180 s) it was demonstrated that the required negative hydrogen current density at an electron to ion ratio well beyond one can be achieved; at the long pulse test facility MANITU [4] (shut down 2011) beam pulses up to one hour were accomplished. In 2012 the test facility ELISE [6] (Extraction from a Large Ion Source Experiment, half size of the ITER source, pulsed beams with a duration of 10 s every 180 s during plasma pulses lasting up to 3600 s) went into operation [7,8].…”
Section: Introductionmentioning
confidence: 99%